Reference intervals for transthoracic echocardiography in the English springer spaniel: a prospective, longitudinal study. (4th August 2016) - Dickson, D.; Shave, R.; Rishniw, M.; Harris, J.; Patteson, M.
Abstract : Objectives: To establish transthoracic echocardiographic reference intervals in adult English springer spaniel dogs. Methods: Forty‐two healthy adult English springer spaniels were prospectively recruited from a general practice population in the UK. Animals were examined twice, at least 12 months apart, to exclude dogs with progressive cardiac disease. Reference intervals were calculated using Box–Cox transformations and specific variables were depicted within an expert consensus range. Relationships of body mass, age and heart rate with cardiac structure and function were examined and functional assessments were compared with previous reports. Reference intervals were compared against published ratiometric indices and allometric scaling models. Results: Thirty‐nine dogs contributed to create the reference intervals. Significant relationships with bodyweight, age and heart rate were detected, although low coefficients of determination were found. Fractional shortening values were lower than has been reported in many breeds but Simpson‐derived ejection fractions were similar to previously published breed‐specific values. Clinical Significance: Breed‐specific reference intervals are reported allowing for more appropriate interpretation of echocardiographic assessments in the English springer spaniel.